To compare the treatment guildlines in line with monitoring ethambutol toxicity - PHIRI GEORGE (Lusaka, the university of Zambia, school of medicine, 2016)
Ethambutol(EMB) is one of the important first line drugs in the treatment of tuberculosis(TB). It is also commonly employed in the treatment of non-tuberculosis mycobacterial infection.
A dissertation submitted in partial fulfilment for the award of bachelor of pharmacy degree at the university of Zambia.
Keywords: Tuberculosis